Integrating DMAIC Six Sigma for Systematic Defect Analysis and Quality Improvement in Manufacturing (Case Study: Rattan Craft Industries) - Adinda Nurlaela; Muchammad Fauzi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study focuses on a rattan-based manufacturing unit producing Base Plant Stand products, where a significant number of defects—2,305 units out of 9,000—were identified, resulting in a current sigma level of 3.14. By employing qualitative and quantitative research approaches, the study aims to identify root causes of product defects and propose process improvements to minimize their occurrence. Using the DMAIC framework of Six Sigma, the most frequent defect types were mold (27.9%), imprecision (22.7%), loose tie (20.9%), and pinhole (15.88%). Key contributing factors included excessive humidity, limited production space, insect infestation, and insufficient operator skills. Based on field research and literature, the proposed improvements include covering products with tarpaulins during rainy conditions, expanding work-in-progress (WIP) space, providing operator training, and developing clear standard operating procedures (SOPs). These recommendations aim to enhance product quality and increase the sigma level through systematic, continuous improvement. The findings are a practical reference for similar small-scale manufacturing operations seeking to optimize their production processes through quality management tools.Keywords: Six Sigma, DMAIC, 5W+1H, Product Defects, Rattan